Nomenclatural acts for some Neotropical Tachinidae (Diptera) - Silvio S. Nihei; Rodrigo de V.P. Dios (Papéis Avulsos de Zoologia)
ABSTRACT New replacement names and synonymies are proposed for Neotropical Tachinidae, mainly from Brazil. The following 13 new replacement names are proposed for junior secondary homonyms: Jurinella neobesa, new name for Jurinella obesa (Townsend, 1928) (preocc. Wiedemann, 1830); Archytas wulpianus, new name for Archytas nigrocalyptratus (Wulp, 1888) (preocc. Macquart, 1846); Calodexia neofumosa, new name for Calodexia fumosa (Townsend, 1917) (preocc. Townsend, 1912); Calodexia bigoti, new name for Calodexia flavipes (Bigot, 1889) (preocc. Schiner, 1868); Eucelatoria paracarinata, new name for Eucelatoria carinata (Townsend, 1927) (preocc. Townsend, 1919); Eucelatoria currani, new name for Eucelatoria carinata (Curran, 1926) (preocc. Townsend, 1919); Lixophaga opsiangusta, new name for Lixophaga angusta (Townsend, 1927:294) (preocc. Townsend, 1927:284); Lixophaga thompsoniana, new name for Lixophaga fumipennis (Thompson, 1968) (preocc. Townsend, 1927); Lixophaga townsendiana, new name for Lixophaga fumipennis (Townsend, 1928) (preocc. Townsend, 1927); Myiopharus argentata, new name for Myiopharus argentescens (Townsend, 1935) (preocc. Townsend, 1927); Phyllophilopsis disgracilis, new name for Phyllophilopsis gracilis (Townsend, 1927) (preocc. Townsend, 1919); Phasia townsendiana, new name for Phasia brasiliana (Townsend, 1937) (preocc. Townsend, 1929); and Phasia aurodysderci, new name for Phasia dysderci (Townsend, 1940) (preocc. Townsend, 1938). And the two following synonymies are proposed (reinstated): Jurinella ambigua (Macquart, 1851) = Jurinella obesa (Wiedemann, 1830); and Archytas analis (Macquart, 1843) = Archytas analis (Fabricius, 1905).